Creative Thinking Skills in Chemistry Learning: A Systematic Literature Review - Sarmila Eka Putri; Vegha Dwi Arthamena; Hana’ Fadhilah Retiyanto; Muhammad Habib Ash Shiddiqi; Suyanta Suyanta (Jurnal Penelitian Pendidikan IPA, 2024)
Creative thinking is one of the abilities needed in facing the 21st century era. Various problems in learning chemistry make students have to be creative thinkers to solve the problems they face. This study aims to determine creative thinking skills in chemistry learning. The method used is Systematic Literature Review (SLR) which adopts 5 stages from Denyer and Tranfield with the criteria of articles on creative thinking skills in learning chemistry indexed by Scopus, Sinta 1, and Sinta 2 from 2014 to 2023, full text and open source. There were 17 articles that fit these criteria. The results of the literature review show that most studies involve chemistry education students as prospective teachers who have an important role in developing students' creative thinking skills. In addition, most studies aim to investigate the effect of learning models on creative thinking skills. Project Based Learning (PjBL) model with a STEM approach is the most effective learning used to improve creative thinking skills with student learning outcomes of 83.00. Based on the results of the literature review, it was found that there is a positive relationship between learning outcomes and creative thinking skills. The better students' learning outcomes, the better their creative thinking skills.